Association of an ACE Gene Polymorphism with Cardiovascular Determinants of Physical Performance in Healthy Iranian Men - Khoshdel 1, Ali Reza; Majidzadeh-A 2, Keivan; Manoochehri 3*, Mehdi (Shahroud Journal of Medical Sciences, 2017)
Background: Physical performance phenotypes are formed by the interaction of genetic and environmental factors, and gene polymorphisms can influence physical and athletic abilities. An ACE gene insertion/deletion (I/D) polymorphism has been reported to influence physical performance, but its mechanism remains controversial.Methods: The frequency of this polymorphism in 146 healthy Iranian males was determined. Then, the associations between different ACE genotypes with physical performance factors were investigated for 43 of the 146 participants.Results: The frequencies of DD, ID and II genotypes were 38.5%, 41.5%, and 20%, respectively. Although there were no significant associations between the ACE polymorphisms and physical performance factors, the pulse pressure amplification, post-exercise heart rate, and resting heart rate were significantly different between variants with and without the I allele (P=0.02, 0.04, and 0.05, respectively). Furthermore, the ACE polymorphism was a significant predictor of exercise endurance and ventricular function in multivariate analyses (P<0.05).Conclusions: The ACE polymorphism correlated with cardiovascular determinants of physical performance, rather than musculoskeletal factors. Therefore, the ACE I/D polymorphism could not be utilized as a singular genetic biomarker for the assessment of physical performance in the Iranian population. However, a combination of genetic and cardiovascular biomarkers may determine physical performance capacities.